2016
DOI: 10.1111/eos.12291
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mechanical properties and bond durability of short fiber‐reinforced resin composite with universal adhesive

Abstract: The purpose of this study was to determine the relationship between mechanical properties and bond durability of short fiber‐reinforced resin composite with universal adhesive. As controls, micro‐hybrid and nano‐hybrid resin composites were tested. The universal adhesives used were Scotchbond Universal, Adhese Universal, and G‐Premio Bond. The fracture toughness and flexural properties of resin composites, and shear bond strength and shear fatigue strength of universal adhesive with resin composite using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…The peak breaking stress and flexural modulus in GPa were determined from the stress-strain curve using a computer with custom software package (Bluehill 2 Ver. 2.5, Instron) linked directly to the testing machine 19) .…”
Section: Flexural Strength Measurementmentioning
confidence: 99%
“…The peak breaking stress and flexural modulus in GPa were determined from the stress-strain curve using a computer with custom software package (Bluehill 2 Ver. 2.5, Instron) linked directly to the testing machine 19) .…”
Section: Flexural Strength Measurementmentioning
confidence: 99%
“…Therefore, the efficacy of silane constituents on the bonding of universal adhesives should be verified. Although several studies have reported the effectiveness of bonding of universal adhesives to zirconia , leucite‐reinforced glass ceramics , and short‐fibre‐reinforced composite resin bonding , few studies have been performed that analyse the efficacy of constituent silane in adhesives. Therefore, to understand the importance of silane, we selected CAD/CAM lithium disilicate glass ceramics and other kinds of universal adhesives as materials.…”
mentioning
confidence: 99%
“…24,27 Furthermore, SFRC can absorb stresses and dissipate energy similar to dentin, 33 improving mechanical performance by preventing brittle failure and preserving structural integrity. 34 The combination of SFRC with an efficient adhesive system could contribute to the high performance obtained in the current study. A two-step etch-and-rinse adhesive was used for two types of composite resins used in this study.…”
Section: Discussionmentioning
confidence: 79%
“…These fibers could provide an isotropic reinforcing effect because each fiber behaves as a crack stopper and stress transfer from the polymer matrix to stronger fibers . Furthermore, SFRC can absorb stresses and dissipate energy similar to dentin, improving mechanical performance by preventing brittle failure and preserving structural integrity . The combination of SFRC with an efficient adhesive system could contribute to the high performance obtained in the current study.…”
Section: Discussionmentioning
confidence: 97%